Efficacy and safety of stem cells in the treatment of glaucoma: systematic review and meta-analysis based on animal experiments - Danning Wu; Yanjing Liu; Xia Zhang; Ruixuan Zhang; Shaopeng Wang; Hui Lu; Tao Yue (Frontiers in Pharmacology)
PurposeGlaucoma, characterized by progressive retinal ganglion cell (RGC) degeneration and optic nerve atrophy, remains a leading global cause of irreversible blindness, despite advancements in clinical management. While current therapies predominantly focus on lowering intraocular pressure (IOP), neuroprotective strategies to preserve visual function remain an unmet clinical need. Stem cells exhibit high proliferative capacity and multilineage differentiation potential, demonstrating notable efficacy in glaucoma treatment. Emerging preclinical evidence further highlights dual neuroprotective mechanisms (i.e., paracrine neurotrophic support and cellular replacement) of stem cell-based interventions. Accordingly, this systematic review and meta-analysis evaluated the therapeutic efficacy and safety of stem cell transplantation in experimental glaucoma models, with a focus on functional outcomes (IOP modulation), structural preservation (RGC survival, and nerve fiber layer integrity), and neuroprotective efficacy.MethodsA systematic literature retrieval from multiple online databases (e.g., PubMed, Web of Science, Embase, Cochrane Library, Scopus, CNKI, WFSD, VIP, and CBM) was conducted through 3 January 2025, to identify relevant animal experimental studies. After the assessment of the risk of bias in the listed articles, this study further computed effect sizes of stem cell transplantation on indices such as IOP, RGC count. Statistical analyses were completed using RevMan 5.3.ResultsIn the meta-analysis involving 19 studies, the stem cell transplantation group had significantly lower IOP (MD = -1.55,95% CI = −2.62 to −0.47) at weeks 3 and 4, higher RGC count at weeks 2, 3, and 4 (MD = 23.06,95%CI = 18.22–27.89), and greater nerve fiber layer thickness (MD = 10.69, 95%CI = 9.44–11.94) compared to the control group. Meanwhile, the stem cell transplantation group also had higher retinal BDNF expression at weeks 2 and 4 (MD = 0.75,95%CI = 0.67–0.83), GDNF expression at weeks 1, 2, 3, and 4, and IGF-1 expression (MD = 0.49,95%CI = 0.39–0.58). None of these studies reported any adverse systemic events.ConclusionThis meta-analysis provides preclinical evidence supporting stem cell transplantation as a multimodal therapeutic strategy for glaucoma, demonstrating significant efficacy in IOP modulation, neurostructural preservation, and neurotrophic factor expression. Given the severity of glaucoma-induced ocular structural damage, it underscores the significance of stem cell transplantation as a secure and promising therapeutic option with notable neuroprotective potential, despite existing translational challenges regarding optimal cell sources, delivery routes, and long-term safety profiles.Systematic Review Registrationwww.inplasy.com, identifier 202520023